2005
DOI: 10.1007/s00438-005-1152-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of alternative translation start sites in the generation of human protein diversity

Abstract: According to the scanning model, 40S ribosomal subunits initiate translation at the first (5' proximal) AUG codon they encounter. However, if the first AUG is in a suboptimal context, it may not be recognized, and translation can then initiate at downstream AUG(s). In this way, a single RNA can produce several variant products. Earlier experiments suggested that some of these additional protein variants might be functionally important. We have analysed human mRNAs that have AUG triplets in 5' untranslated regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 35 publications
3
60
0
1
Order By: Relevance
“…(41,(65)(66)(67)(68)(69) For example, 44% of 5 0 -UTRs in a human mRNA sample contained uAUGs (18% of them contained three or more uAUGs). (67) Analysis of a sample of mouse mRNAs with a single uAUG showed that the average size of a uORF-encoded peptide was 21 amino acids, and 411 uORF-encoded peptides were larger than 50 amino acids; that is, these peptides can be considered as small proteins (for example, ROT4 and DVL1 genes encode important regulatory proteins of 53 and 51 amino acids, respectively). (60,61,70) Second, eukaryotic mRNAs are frequently characterized by a suboptimal context of annotated TIS (i.e.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
See 2 more Smart Citations
“…(41,(65)(66)(67)(68)(69) For example, 44% of 5 0 -UTRs in a human mRNA sample contained uAUGs (18% of them contained three or more uAUGs). (67) Analysis of a sample of mouse mRNAs with a single uAUG showed that the average size of a uORF-encoded peptide was 21 amino acids, and 411 uORF-encoded peptides were larger than 50 amino acids; that is, these peptides can be considered as small proteins (for example, ROT4 and DVL1 genes encode important regulatory proteins of 53 and 51 amino acids, respectively). (60,61,70) Second, eukaryotic mRNAs are frequently characterized by a suboptimal context of annotated TIS (i.e.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
“…(67,(69)(70)(71) The positional frequencies of AUG codons at the beginning of coding sequences of mouse mRNAs in samples with optimal and suboptimal start codon contexts are shown on Fig. 3.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional constraints on non-3n indels unrelated to peptide coding may have separated strict uORFs from the other two types of uORFs. Another explanation is that overlapping uORFs can give rise to in-frame N-truncated peptides, which may have different molecular functions from the original, full-length peptides [17]. Such N-truncated peptides may change in length or simply disappear if non-3n indels occur downstream of VuAUGs.…”
Section: Discussionmentioning
confidence: 99%
“…The ribosomal complexes then slide from 5'-cap to 3' end base by base until they encounter the first AUG triplet of the mRNA and turn on the translation process. According to this model, different types of uORF have distinct effects on the translation of the main CDS: (1) strict uORFs compete for ribosomes, leading to reduced protein production of the main CDS [16]; (2) overlapping uORFs cause translation re-initiation downstream of the main start codon, resulting in N-truncation of the peptide coded by the main CDS [10,17]; they may also cause strong translational inhibition by facilitating ribosome skipping of the main start codon [10,18,19]; and (3) alternative uORFs result in the generation of N-extended peptides [17,20,21]. Notably, non-3n indels downstream of uAUGs can lead to interchanges between uORF types (Figure 1B), while 3n indels usually can not.…”
Section: Introductionmentioning
confidence: 99%